Type I interferons in bacterial diseases: myeloid cells at the crossroads of protection and pathology - Lyadova, Irina (Frontiers in Immunology, 2026)
Type I interferons (IFN-I) are multifunctional cytokines with well-established antiviral and antitumor activities. In viral infections and cancer, IFN-I are largely protective, acting through both direct mechanisms, such as induction of antiviral or antiproliferative programs, and indirect mechanisms, mediated through the activation of immune effector cells. During bacterial infections, IFN-I primarily act indirectly, making their role more complex and contradictory. Depending on the context, IFN-I may promote host protection or contribute to pathology, and factors determining these divergent outcomes remain poorly understood. Comparative analysis of existing studies indicates that discrepancies in IFN-I effects arise from multiple pathogen- and host-dependent factors, including pathogen biology, the route of pathogen delivery, infection stage, host immune competence, the magnitude of IFN-I response and other parameters. Among them, the ability of IFN-I to reprogram myeloid cell responses appears to be a critical but insufficiently characterized determinant. This review synthesizes current evidence on IFN-I responses in bacterial infections, with particular emphasis on their effects in the myeloid cell compartment. These include IFN-I ability to inhibit macrophage activation, alter macrophage metabolism, induce myeloid cell death, affect macrophage and neutrophil recruitment, and modulate myeloid cell generation by supporting emergency hematopoiesis and redirecting lineage output toward monocyte or granulocyte generation. Given that macrophages and neutrophils differentially contribute to protection or pathology across various bacterial infections, such effects may underlie both beneficial and detrimental outcomes of IFN-I signaling. The review highlights IFN-I-driven regulation of myeloid cell activity and myelopoiesis as overlooked checkpoints in bacterial pathogenesis, providing a framework for future mechanistic studies and guiding the search for new opportunities in therapeutic intervention.